2006
DOI: 10.1534/genetics.105.054072
|View full text |Cite
|
Sign up to set email alerts
|

Hos2 and Set3 Promote Integration of Ty1 Retrotransposons at tRNA Genes in Saccharomyces cerevisiae

Abstract: The yeast LTR retrotransposon Ty1 integrates preferentially into regions upstream of tRNA genes. The chromatin structure of transcriptionally active tRNA genes is known to be important for Ty1 integration, but specific chromatin factors that enhance integration at tRNA genes have not been identified. Here we report that the histone deacetylase, Hos2, and the Trithorax-group protein, Set3, both components of the Set3 complex (Set3C), enhance transposition of chromosomal Ty1 elements by promoting integration int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 49 publications
0
63
0
Order By: Relevance
“…TIG1 and its orthologs are conserved from yeast to human (Pijnappel et al, 2001;Mou et al, 2006). TIG1 shares higher similarity with mammalian TBL1 than with yeast SIF2.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…TIG1 and its orthologs are conserved from yeast to human (Pijnappel et al, 2001;Mou et al, 2006). TIG1 shares higher similarity with mammalian TBL1 than with yeast SIF2.…”
Section: Discussionmentioning
confidence: 98%
“…SMRT proteins have an N-terminal domain that binds to nuclear receptors and a C-terminal region that interacts with HDACs. In yeast, Sif2 is a component of the Set3 HDAC complex that consists of Sif2, Hos2, Set3, Snt1, Hst1, Hos4, and Cpr1 (Pijnappel et al, 2001;Cerna and Wilson, 2005;Mou et al, 2006). Several of these proteins are conserved from yeast to human.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e l s e v i e r . c o m / l o c a t e / g e n e eukaryotic genomes suggests target-site specificity (Kim et al, 1998 (Bachman et al, 2005;Mou et al, 2006;Yieh et al, 2000Yieh et al, , 2002. Movement of TEs within a genome can change chromosome structure (Eichler and Sankoff, 2003;Feschotte and Pritham, 2007;Kidwell and Lisch, 2001) and modulate the expression of nearby protein coding genes (Feschotte, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of examples involving integrases from yeast LTR retrotransposons have also shown that retroviral-like integrases have evolved to acquire strong site-specific integration properties (Sandmeyer 2003;Zhu et al 2003;Brady et al 2008;Gao et al 2008). For example, the integration of Saccharomyces cerevisiae retrotransposons Ty1 and Ty3 is associated with RNA polymerase III transcription (Yieh et al 2000;Bachman et al 2005;Mou et al 2006) and the Tf1 retrotransposon from Schizosaccharomyces pombe integrates near RNA polymerase II promoters (Singleton and Levin 2002;Bowen et al 2003). In other examples, transposable elements are targeted to heterochromatic sites by tethering mechanisms involving interactions between the integrase and DNA binding proteins.…”
mentioning
confidence: 99%